2002
DOI: 10.1148/radiographics.22.5.g02se191077
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Arterial Chemoembolization for Hepatocellular Carcinoma: Anatomic and Hemodynamic Considerations in the Hepatic Artery and Portal Vein

Abstract: Hepatocellular carcinoma (HCC) is the most common malignant tumor of the liver. Although several therapeutic options have been advocated, transcatheter arterial chemoembolization (TACE) in particular has been widely performed in the treatment of HCC. Still, hepatic arteriography and portography are mandatory for evaluation of (a) the resectability and multiplicity of HCCs and (b) the hemodynamic status of the portal vein. Thereafter, TACE can be considered as the initial therapeutic modality. The possibility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…in case of uterine fibroid embolization), while an undesired expansion of the necrotic region would originate from uncontrolled over-embolisation (Chua et al 2005;Liapi et al 2007). Non-target embolisation was also responsible for flow reversal in collateral arteries or, in the worst case, could lead to organ failures (Lee et al 2002;Moreira and An 2003;Wolanske et al 2003). In addition, a comprehensive understanding of the principles governing microparticle performance is a necessary prerequisite for improving the process flexibility and designing patient-specific embolisation protocols.…”
Section: Introductionmentioning
confidence: 99%
“…in case of uterine fibroid embolization), while an undesired expansion of the necrotic region would originate from uncontrolled over-embolisation (Chua et al 2005;Liapi et al 2007). Non-target embolisation was also responsible for flow reversal in collateral arteries or, in the worst case, could lead to organ failures (Lee et al 2002;Moreira and An 2003;Wolanske et al 2003). In addition, a comprehensive understanding of the principles governing microparticle performance is a necessary prerequisite for improving the process flexibility and designing patient-specific embolisation protocols.…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of this variation is important in presurgical planning of liver transplantation, tumour resection, laparoscopic hepatobiliary surgery, hepatic artery infusion chemotherapy and transarterial chemo-embolization [13].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic parenchymal atrophy, a well-known complication of TACE, is related to ischaemic injury, especially in patients with decreased portal venous perfusion caused by thrombosis or in those who have undergone repeated embolization [6]. The results of numerous investigations have demonstrated that TACE-induced bile duct injury compromises the alongside portal venous inflow, which is related to the portal tract inflammation from chemical and ischaemic insult by embolic materials or extravasated bile, leading to phlebitis and thrombus formation in addition to biloma or dilated intrahepatic bile duct radicles compressing the lower-pressure portal venous radicles [13,16].…”
Section: Discussionmentioning
confidence: 99%
“…Among the various complications of TACE for the nontumorous hepatic parenchyma [6,7], THADs appear not infrequently on the follow-up dynamic imaging studies. Aside from the diagnostic challenge for a differential diagnosis between the viable tumour tissue and THAD itself, according to our experience over the past decades, we realized that the TACE-related THAD could be related to the subsequent non-tumorous parenchymal changes depending on the presence of biliary or vascular injuries.…”
Section: Introductionmentioning
confidence: 99%